Allergy to oxidized limonene and linalool is frequent in the U.K. (26th July 2014) - Audrain, H.; Kenward, C.; Lovell, C.R.; Green, C.; Ormerod, A.D.; Sansom, J.; Chowdhury, M.M.U.; Cooper, S.M.; Johnston, G.A.; Wilkinson, M.; King, C.; Stone, N.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Limonene and linalool auto‐oxidize upon exposure to air and their oxidation products can cause contact allergy. A significant rate of allergy to oxidized limonene and linalool has been shown in multicentre European studies and one small, single‐centre U.K. study. What does this study add? This is the first multicentre audit to show a significant rate of allergy to oxidized terpenes throughout the U.K. There is a high rate of irritant reactions to the oxidized terpenes. We recommend that oxidized limonene and linalool be added to an extended baseline patch test series in the U.K. The optimum concentration of the terpene hydroperoxides for patch testing has yet to be determined.